Pengaruh Jumlah Kendaraan Bermotor Dengan Kadar Karbon Monoksida (CO) Di Udara Pada Jalan Perintis Kemerdekaan Dan Jalan Lubuk Begalung - Sari, Dwi Dhiya; Irfan, Asep; Muslim, Burhan; Seno, Basuki Ario (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Padang, 2023)
Vehicles with low speed will produce more exhaust emissions, especially CO gas. Exposure to air with CO gas can cause poisoning of the central nervous system and heart. This study aims to determine the effect of the number of motorized vehicles with levels of carbon monoxide (CO) in the air on Jalan Perintis Kemerdekaan and Jalan Lubuk Begalung, Padang City in 2022. The type of research used was analytical observational using a correlation test with a cross sectional design with a sample of 5 samples. Times per day at the same time. The results showed that Carbon Monoxide levels were positively correlated to the increase in the number of motorized vehicles with a value of r = 0.9. The number of motorized vehicles on Lubuk Begalung street is lower, humidity and wind speed are lower, the temperature is higher, while the number of motor vehicles on Jalan Perintis Kemerdekaan is higher, humidity and wind speed are higher and temperature are low. Carbon Monoxide levels on Jalan Perintis Kemerdekaan were higher at 3.242 ug/Nm3 and on Lubuk Begalung street at 2.572 ug/Nm3. For this reason, it is necessary to improve the quality of public transportation power by checking and repairing public transportation and reducing the use of privite vehicles and making green efforts on roads that can absorb pollutants to reduce the impact of motor vehicle exhaust emissions.